Subjetividade, liberdade e existência: aproximações e distanciamentos entre Sartre e Rogers - Cruz, Bruno Alves de Araújo (2009)
This work reflects the dialogue’s century XIX between philosophy and psychology, when the latter sought to achieve scientific status, and defined its object of study. This return is due to the fact that new science, seeking its place among the other, stay away from their original object in order to adapt the methods of positive science, which eventually led to the objectivism behavior. Also due to the fact that the philosophy does not leave the task of understanding the subjectivity, especially the phenomenological tradition. Moreover, it is justified to see that the psychology, developed in the clinic, does not leave the understanding of subjectivity, since it considers as a fundamental element of the human relationship with the world. To resume the dialogue between philosophy and psychology, seeks to bring to psychology the opportunity to understand what had been its original object. To achieve this dialogue, we chose to use the work of the philosopher Jean-Paul Sartre and the psychotherapist Carl R. Rogers, with the objective of pointing between the two thinkers and distances the approximations in the treatment of the concepts of subjectivity, freedom and existence. In making the works of Sartre, it was found that the subjectivity and spirit has the freedom, which is the annihilation through which you can open a crack in its interior, including the not in his being, enabling it to support itself from the choices you make to your life. Therefore, Sartre points to the indeterminacy that is the relation of subjectivity to their being and the world, since "the existence precedes essence." In Rogers, it was found that subjectivity is fundamental to achieving the organic trend, as is the freedom that allows you to choose various ways to meet their needs and thus realize all possible organic.